Using a Mindfulness-Based Intervention to Promote Subjective Well-Being, Trait Emotional Intelligence, Mental Health, and Resilience in Women With Fibromyalgia - Cejudo, Javier; García-Castillo, Francisco-Javier; Luna, Pablo; Rodrigo-Ruiz, Débora; Feltrero, Roberto; Moreno-Gómez, Alfonso (Frontiers in Psychology, 2019)
The objective of the present study was to experimentally assess the effects of a mindfulness-based intervention for the improvement of subjective well-being, trait emotional intelligence, mental health, and resilience in a sample of women with fibromyalgia. The sample consisted of 104 women, between 29 and 57 years old (M = 47.59; SD = 5.93). The measures used were as follows; Satisfaction with Life Scale (SWLS), Positive and Negative Affection Scale (PANAS), Trait Emotional Intelligence Questionnaire - Short Form (TEIQue-SF), Mental Health Questionnaire (MH-5) and Resilience Scale (ER-14). A quasi-experimental design of repeated measures with a control group was used: before and after the application of the treatment and a follow-up assessment 6 months after the completion of the intervention. In order to assess the effect of the program, the participants were randomly assigned to the experimental and control conditions. In the pretest evaluation, a Multivariate Analysis of Variance (MANOVA) and Analysis of Variance (ANOVA) were carried out. In the post-test evaluation, a Multivariate Analysis of Covariance (MANCOVA) of the study variables as a whole was performed. Then, descriptive analyses and analysis of covariance (ANCOVA) of the post-test scores (covariate pretest score) were performed. In the follow-up evaluation, a MANCOVA of the study variables as a whole was performed. Then, descriptive and ANCOVA analyses of the follow-up scores (covariate pretest score) were performed. In addition, the effect size was calculated using partial eta-squared (η2). The post-test results confirmed statistically significant differences in satisfaction with life, positive affect, mental health, and resilience. The follow-up results showed statistically significant differences in satisfaction with life, positive affect, trait emotional intelligence, mental health, and resilience. The study provides an effective intervention tool that has been validated experimentally. The general results allow the emphasis of the importance of the implementation of Mindfulness-based interventions framed in non-pharmacological treatments in fibromyalgia.